Effect of reactor characteristics on the seasonal effectiveness of solar disinfection: a factorial study - Ekene Jude Nwankwo; Jonah Chukwuemeka Agunwamba (Water SA, 2021)
Solar disinfection (SODIS) involves exposing water stored in transparent polyethylene terephthalate (PET) containers to the sun for about 6 h of strong sunlight, after which the water is rendered safe for consumption. This study investigated the seasonal effect of reactor characteristics on the inactivation kinetics/constant of faecal coliforms by conducting a 23 factorial experiment, involving two levels of PET bottle size, PET bottle thickness, and PET bottle rear surface, uniquely combined to form 8 SODIS reactors/experimental units. The faecal coliform population of hourly samples taken from the 8 SODIS reactors showed that the inactivation kinetics/constant depends on the irradiation energy and maximum water temperature as dictated by the reactor characteristics. The average rate constant of the reflective reactors (1.37 ± 0.43 h-1) was significantly better (p < 0.001) than the absorptive reactors (1.17 ± 0.59 h-1) between June and October. The average rate constant of the small PET bottles (1.73 ± 0.65 h-1) is significantly higher (p < 0.002) than the large PET bottles (1.46 ± 0.51 h-1) from December to May; while the average rate constant of the light PET bottles (1.58 ± 0.64 h-1) is significantly better (p < 0.001) than the thick PET bottles (1.41 ± 0.52 h-1) year-round. Analyses of results confirmed a two-way interaction effect between PET bottle size and PET bottle thickness and between PET bottle rear surface and PET bottle thickness for periods with average radiation intensity of  450–500 W∙m−2. Although container size and thickness were the most significant factors, combining light PET bottles with absorptive rear-surface could extend the applicability of SODIS to regions that fall short of the recommended radiation intensity threshold of 500 W∙m−2 for 5 h.